Sir Edwin Arnold papers - Arnold, Edwin, Sir, 1832-1904.
Epic poem titled, Light of Asia, concerning Guatama Buddha and a letter of presentation from Arnold to Andrew Carnegie.
Poet, journalist and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Gautama Buddha; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Buddhism; Religious poetry; India -- Religion; Educators; Journalists; Poets